ANALISIS KEMAMPUAN MEMBACA CEPAT DAN PEMAHAMAN PADA SISWA KELAS IV SD NEGERI KARANG TENGAH 12 KOTA TANGERANG - Salsabilah, Salsabilah; latifah, Nur; Magdalena, Ina (Pendidikan Dasar - Pascasarjana Universitas Negeri Jakarta, 2023)
This study aims to determine the speed reading skills and comprehension of fourth grade students at Karang Tengah 12 Public Elementary School, Tangerang City. This research uses a qualitative approach with descriptive methods. Data collection techniques used are tests, observations, interviews and documentation. The subjects of this study were fourth grade students at Karang Tengah 12 Public Elementary School, Tangerang City. The results of this study indicate that almost all students' speed reading skills and comprehension are good, but there are some students whose reading skills are still lacking, namely in reading fluency, reading intonation, sentence use, punctuality, confidence, not being able to read text correctly and clearly, answering questions related to the text, explaining the meaning contained in the reading, interpreting difficult words in the reading text and transcribe information in reading.